Modeling tangential flow filtration using reverse asymmetric membranes for bioreactor harvesting. (3rd October 2020) - Zhang, Da; Patel, Parag; Strauss, Daniel; Qian, Xianghong; Ranil Wickramasinghe, S.
Abstract: Tangential flow filtration (TFF) has many advantages for bioreactor harvesting, as the permeate could be introduced directly to the subsequent capture step. However, membrane fouling has limited its widespread use. This is particularly problematic given the high cell densities encountered today. Here, a reverse asymmetric membrane, where the more open surface faces the feed stream and the tighter barrier layer faces the permeate stream, has been investigated. The open surface contains pores up to 40 μm in diameter while the tighter barrier layer has an average pore size of 0.4 μm. Filtration of yeast suspensions has been conducted under a range of conditions. The yeast cells are trapped in the open pore structure. The membrane stabilizes an internal porous cake that acts like a depth filter. This stabilized cake layer can remove particulate matter that would foul the barrier layer if it faced the feed stream. As filtration continues, a surface cake layer forms on the membrane surface. A resistance in series model has been developed to describe the permeate flux during TFF. The model contains three fitted parameters which can easily be determined from constant pressure normal flow filtration experiments and total recycle constant flux TFF experiments. The model can be used to estimate the capacity of the filter for a given feed stream. Our results suggest that using a reverse asymmetric membrane could avoid severe flux decline associated with fouling of the barrier layer during bioreactor harvesting.